2017
DOI: 10.17475/kastorman.283249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Fire Retardant Chemicals in Different Concentrations on Formaldehyde Emission of Plywood

Abstract: Aim of study: Although treated panels make up a large portion of the plywood market, treatment with some wood preservatives has been known to cause some problems such as bonding failures besides the environmental pollution related to the disposal of chemicals after treatment. Formaldehyde release from wood based panels is also another problem regarding the indoor air quality. In the present study, it was aimed to investigate the formaldehyde emission contents of plywood panels treated with fire retardant chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(6 reference statements)
0
4
0
2
Order By: Relevance
“…ANN models were trained and tested with the data obtained from the experimental results of Demir et al (2016). Change of retention level depending on the wood species and concentration were modelled with obtained network parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANN models were trained and tested with the data obtained from the experimental results of Demir et al (2016). Change of retention level depending on the wood species and concentration were modelled with obtained network parameters.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the experimental results obtained from the study of Demir et al (2016) were used. Therefore, the authors acknowledge Dr. Aydin Demir, Dr. Ismail Aydin, and Dr. Semra Colak for enabling data to be used.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…When flours are added as fillers for an adhesive, the rheological behavior and the curing properties of the adhesive are changed [23]. Previous studies have shown that the flame retardant containing phosphorus often leads to a bonding strength reduction [24]. In this work, wet shear strength of the plywood was evaluated using various ratios of MUF and IFR.…”
Section: Shear Strength Testmentioning
confidence: 99%
“…Yangın geciktirici kimyasalların, kendileriyle işlenen malzemelerin diğer fiziksel, mekanik ve bazı teknolojik özellikleri üzerinde etkili olduğu bilinmektedir (Ustaömer, 2008). Tarafımızca yapılan bir çalışmada, bazı yangın geciktirici kimyasalların konsantrasyon ile retensiyon miktarlarına bağlı olarak kontrplakların formaldehit emisyonunu azalttığı bazılarının ise arttırdığı tespit edilmiştir (Demir et al, 2017).…”
unclassified
“…Tablo 4'teki verilere göre, her üç ağaç türünde çinko borat ile emprenye işleminin kontrplakların formaldehit emisyonlarını konsantrasyon ve retensiyona bağlı olarak artırmaya devam ettiği gözlemlenmiştir.Çolak & Çolakoğlu (2004) borik asidin panellerin formaldehit emisyonlarını arttırdığını bulmuşlardır. Tarafımızca tapılan önceki çalışmada da benzer şekilde çinko boratın da kontrplağın formaldehit emisyonunu artırıcı etkisi olduğu bulunmuştur(Demir et al, 2014). Literatürde yapılan bu çalışmalarda, yangın geciktirici kimyasalların katkı oranlarının artmasına bağlı olarak formaldehit emisyonlarının da daha fazla değiştiği tespit edilmiştir.SONUÇBu çalışmada, ağaç türü, yangın geciktirici kimyasal madde türü ve çözelti konsantrasyonu değişkenlerinin kontrplakların retensiyon miktarları üzerine etkileri ile ağaç türü, yangın geciktirici kimyasal madde türü, çözelti konsantrasyonu ve retensiyon miktarı değişkenlerinin formaldehit emisyonu üzerine etkilerini modellemek için YSA analizleri gerçekleştirilmiştir.…”
unclassified